Dampak Penerapan Desain Cara Kerja terhadap Beban Kerja pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Provinsi Kepulauan Riau - Hasim As’ari (Jurnal Ekonomi KIAT, 2018)
This research raises the issue of the application of the work method design to the workload of the Human Resources and Human Resources Development Agency of Kepulauan Riau Province. Workload in the Human Resources and Human Resources Development Agency of Kepulauan Riau Province has not been able to shape the character of work efficiently and effectively as the purpose of the workload is to improve organizational performance. Research uses qualitative research methods, which are focused on the implementation of the design of the work of the impact on the implementation of workloads, especially on the elements that make up the workload analysis within the Human Resources and Human Resources Development Agency. The results showed that the design of the work method has not been able to streamline work services because it is still focused on the procedural system and management rigidity, so that the workload that is used as a basis for workload analysis has not shown results in the context of administrative services and human resource development.